Chiti, Martini e gli albori della storia della musica - Arnaldo Morelli (Artes)
Girolamo Chiti (1679-1759), maestro di cappella at San Giovanni in Laterano and epigone of the so-called “Roman school”, was one of the most assiduous correspondents of Father Giambattista Martini. Indeed, the two exchanged over four hundred letters in the course of fourteen years, between 1745 and 1759. Based on an examination of this correspondence, the article scrutinizes the fundamental help Chiti offered to Martini in preparing his Storia della musica, on the one hand helping to locate and continuously sending precious materials such as treatises on musical theory and ancient and modern compositions while on the other hand engaging in a fruitful exchange of ideas on music, especially sacred music. Although both were convinced that the foundation of composition lay in counterpoint treatises and sixteenth-century polyphony, the ideas and work of Chiti and Martini reveal that they were not conservatives, opponents of modernity, but rather two personalities participating in an authentic eighteenth-century spirit.